2022
DOI: 10.1155/2022/7624135
|View full text |Cite|
|
Sign up to set email alerts
|

An Early Warning Risk and Control Model for Manpower Capital Investment Using Data Warehousing and Computational Intelligence

Abstract: Human capital plays an important role in the development of enterprises. Investing in human capital is the main focus of enterprises to improve personnel quality and enhance their core competitiveness. With the development of market economy, the function of human resource market allocation has been improved and the mobility of enterprise human resources has been enhanced leading to the increase in investment risk of enterprise human capital. Enterprise human capital investment risk has a negative impact on ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Employee health and well-being has a significant impact on MSME performance (Yu, 2013). Research has shown that positive employee health, including physical and mental well-being, is associated with increased work engagement and performance (Liu & Wang, 2022). Organizations that prioritize employee health and well-being can benefit from reduced personnel costs and increased productivity (Saeed et al, 2015).…”
Section: ) Employee Health and Welfarementioning
confidence: 99%
“…Employee health and well-being has a significant impact on MSME performance (Yu, 2013). Research has shown that positive employee health, including physical and mental well-being, is associated with increased work engagement and performance (Liu & Wang, 2022). Organizations that prioritize employee health and well-being can benefit from reduced personnel costs and increased productivity (Saeed et al, 2015).…”
Section: ) Employee Health and Welfarementioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%